2009
DOI: 10.14411/eje.2009.027
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive patterns in the millipede Polydesmus angustus (Diplopoda: Polydesmidae) and their significance for cohort-splitting

Abstract: Abstract. First-stadium juveniles of Polydesmus angustus born each month from May to September were reared throughout their life cycle under controlled seasonal conditions. At maturity, the reproductive patterns of 62 females were studied individually. It was confirmed that females born from May to August have a 1-year life cycle and those born from late August onwards a 2-year life cycle (cohort-splitting). A third type of life cycle -interseasonal iteroparity -was observed in a few females born late in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The extended life cycle results from a delay in development, due to aestivation in stadium VII, combined with the adult females overwintering in reproductive diapause. In a previous study, it was shown that biennial offspring are produced almost exclusively by annual females, so this pattern cannot be determined genetically (David, 2009). In the present study the hypothesis that the propensity of late-born individuals to aestivate results, at least in part, from a non-genetic maternal effect, was tested.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The extended life cycle results from a delay in development, due to aestivation in stadium VII, combined with the adult females overwintering in reproductive diapause. In a previous study, it was shown that biennial offspring are produced almost exclusively by annual females, so this pattern cannot be determined genetically (David, 2009). In the present study the hypothesis that the propensity of late-born individuals to aestivate results, at least in part, from a non-genetic maternal effect, was tested.…”
Section: Discussionmentioning
confidence: 98%
“…This species has a long period of reproduction in spring-summer, during which each female produces several broods at intervals of a few weeks before dying (David, 2009). Eggs are laid in nests made of earthy faecal material, and first stadium juveniles leave the nest soon after hatching.…”
Section: Biological Materialsmentioning
confidence: 99%
See 3 more Smart Citations